Die intra- und extraregionalen Beziehungen der südpazifischen Inselstaaten - Buchholz, Hanns Jürgen (ERDKUNDE, 1988)
The spatial pattern and the direction of political and economic inter-relations of the South Pacific have passed through several stages: (i) from a widely dispersed and unconnected mosaic of many political micro-units with more or less no extra-regional inter-relations via (ii) the large colonial regionalization, attaining after World War II a tripartition of the whole area and respectively strong links with the U.S.A., to the United Kingdom and to France until (iii) the present stage of fragmented, mainly self governing entities, resulting from the decolonization process since 1962. The extra-regional linkages generally still show the colonial dependence. The coming network of intra- and extra-regional inter-relations should be conditioned from the desire of the South Pacific island-countries to overcome their problem of smallness and the danger of losing the critical mass needed for autonomous development: by an intensification of the intra-regional co-operation and by the diversification of the extra-regional relation to as many states as possible in order to neutralize - wherever possible - external pressure and to optimize the influx of foreign assistance.